2000
DOI: 10.1046/j.1439-0272.2000.00398.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of two complex platinum salts on human sperm motility and acrosome reaction

Abstract: Hydrogen hexachloroplatinate, H2PtCl6, has been shown to induce the human sperm acrosome reaction in vitro. However, the molecular mechanism underlying this exocytic process has not been studied. Therefore, two structurally and chemically different platinum (Pt) compounds, the potent sensitizer sodium-hexachloro-platinate-(IV), Na2[PtCl6], and the nonimmunogenic tetraamineplatinum-(II)-chloride, [Pt(NH3)4]Cl2, were selected for the experiments. Their effects on human sperm function and second messenger pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…In our study, we demonstrated that cisplatin can adversely affect the motility of human sperm, which was consistent with previous reports [8]. Furthermore, we showed that a low dose of melatonin markedly alleviated the observed decrease in the motility of human sperm caused by cisplatin.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, we demonstrated that cisplatin can adversely affect the motility of human sperm, which was consistent with previous reports [8]. Furthermore, we showed that a low dose of melatonin markedly alleviated the observed decrease in the motility of human sperm caused by cisplatin.…”
Section: Discussionsupporting
confidence: 93%
“…Mature human sperm have 22-28 mitochondria helically arranged around the axoneme of the sperm, which generate ROS and ATP to maintain sperm motility. These mitochondria are potential targets of cisplatin [7,8]. Therefore, it is desirable to find an effective therapy to protect sperm against cisplatin.…”
Section: Introductionmentioning
confidence: 99%